2016
DOI: 10.5267/j.esm.2016.2.001
|View full text |Cite
|
Sign up to set email alerts
|

Friction stir welding of dissimilar Al alloys: effect of process parameters on mechanical properties

Abstract: In the present experimental study, two dissimilar sister aluminum alloys, 5083 and 5086, are welded through friction stir welding process. Different experiments are conducted on vertical milling machine through a fixture design and firm holding welding plates on it. These experiments are performed by varying welding parameters including welding speed, rpm, different pin profiles, tool tilt angle at five levels each. Two different mechanical properties of the welded specimen (i.e. tensile strength and percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Nine experiments have been conducted with the various symmetric combination of TRS and TS on a modified vertical milling machine. Other input process parameters have been fixed at economical levels based upon review of literature (Vijay and Murugan 2010, Kuram and Ozcelik 2013, Deepandurai and Parameshwaran 2015, Kundu and Singh 2016. Input tool tilt angle has been fixed as 2˚ and the initial force has been kept 6 KN.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine experiments have been conducted with the various symmetric combination of TRS and TS on a modified vertical milling machine. Other input process parameters have been fixed at economical levels based upon review of literature (Vijay and Murugan 2010, Kuram and Ozcelik 2013, Deepandurai and Parameshwaran 2015, Kundu and Singh 2016. Input tool tilt angle has been fixed as 2˚ and the initial force has been kept 6 KN.…”
Section: Methodsmentioning
confidence: 99%
“…After generating enough frictional heat it starts to move in transverse direction on the pre-defined weld line. Different research investigations have been carried out for efficient joining to make it valuable over other joining processes (Gibson et al, 2014;Shultz et al, 2013;Yuan et al, 2012;Patel et al, 2015;Kundu & Singh, 2016). Joint properties for different conditions like corrosion are studied which have myriad of benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Welding technology, joining method, and the effect of process parameters on mechanical properties are very important to predict the fatigue life of welded structures. A review of the above‐mentioned aspects of welding can be found in previous studies …”
Section: Introductionmentioning
confidence: 99%
“…porosity, cracking, blow holes which appear during conventional fusion welding process are avoided (Cavaliere, 2013;Kevorkijan, 2002;Khodaverdizadeh, Mahmoudi, Heidarzadeh, & Nazari, 2012;Kundu & Singh, 2016;Taban & Kaluc, 2006). In friction stir welding, high temperature below the melting point is attained through friction between tool shoulder and joining sheets as well as frictional heat produced by tool pin and the semi-solid material through the plastic flow of materials under the tool shoulder.…”
Section: Introductionmentioning
confidence: 99%